Types of Addiction: Vulnerability Among Adolescents andYouth in Palestine Today - Dr. Jawad Fatayer (My University, 2010)
Purpose:
The purpose of this work is to introduce a new diagnostic tool which specifies types of addiction, thus enhances the treatment outcomes and assures effective policies.
Methods:
This work is based on over 20 years of clinical practice and therapeutic intervention in USA and few Arabic countries. Nearly 500 cases of adolescents and youth were treated using CEBT.
Results:
Therapy works with this age group despite challenges. Identifying addiction types helps treatment efforts and encourages individual‟s response to treatment.
Conclusion:
Treating all addiction types as one is unscientific neither helpful to patients. Certain socio-emotional forces are to be considered when addiction is addressed.

Purpose:
The purpose of this work is to introduce a new diagnostic tool which specifies types of addiction, thus enhances the treatment outcomes and assures effective policies.
Methods:
This work is based on over 20 years of clinical practice and therapeutic intervention in USA and few Arabic countries. Nearly 500 cases of adolescents and youth were treated using CEBT.
Results:
Therapy works with this age group despite challenges. Identifying addiction types helps treatment efforts and encourages individual‟s response to treatment.
Conclusion:
Treating all addiction types as one is unscientific neither helpful to patients. Certain socio-emotional forces are to be considered when addiction is addressed.
Types of Addiction: Vulnerability Among Adolescents andYouth in Palestine Today